Comparison of frequency-specific c-Fos expression and fluoro-2-deoxyglucose uptake in auditory cortex of gerbils (meriones unguiculatus) - Zuschratter, Werner; Gass, Peter; Herdegen, Thomas; Scheich, Henning (European journal of neuroscience, 1995)
Induction of c-Fos in the auditory cortex of gerbils was investigated immunocytochemically 1 h after single, triple or 1 h continuous stimulation with a series of narrow band frequency-modulated tone bursts. With single stimulation c-Fos immunoreactive neurons were chiefly found in the primary auditory field (AI), where they formed a narrow frequency-specific column across layers II-VI. Side-band-like patterns adjacent to this column appeared characteristically with triple stimulation. Immunoreactive cell density in the anterior auditory field and the caudal fields was sparse and location not frequency specific with single or triple stimulation. Spatial comparisons of c-Fos immunoreactive neuron density with 2-deoxy-2-fluoro-D-glucose (FDG) autoradiography in the same animals after 1 h of stimulation revealed spreading of c-Fos expression in neurons across the tonotopic maps of the Al and in the rostral and caudal fields of the auditory cortex. The pattern of the highest density of c-Fos labelled cells in the Al still matched the peak labelling of FDG autoradiographs. The results show that the postsynaptic marker c-Fos reflects the frequency representation in the Al with single or triple stimulation yet with a higher spatial resolution than the deoxyglucose technique. Longer stimulation causes non-tonotopic intracortical spreading of the c-Fos-inducing message, a phenomenon potentially reflecting the effects of cooperativity in the maps.